THE IMPACT OF ‘KOREAN WAVE’ ON YOUNG INDONESIAN FEMALES AND INDONESIAN CULTURE IN JABODETABEK AREA - Putri, Vandani Kencana; Reese, Matthias (Academic Research Centre Services, 2016)
Popular culture ?Korean Wave? has been reaching out all over the world since the year 2000 with the phenomenon intriguing people?s interests towards Korean culture and products. In fact, some people already prefer Korean culture and products to those from their own country. It is inevitable in Indonesia, too, where most of its K-Wave-enthusiasts are teenage to adult females. With this in mind, there is a possibility that Indonesian culture might eventually vanish in those individuals. Thus, this quantitative research focuses on Indonesian female K-Wavers between 15 and 30 years old who are living in the Jabodetabek area, and investigates their main medium of Korean Wave consumption and whether Korean Wave has an impact on individuals and on Indonesian culture itself. The results based on the data of 251 respondents show that internet is the main medium of Korean Wave consumption in the Jabodetabek area. Furthermore, the results injdicate that the Korean Wave does significantly impact Indonesian female K-Wavers in several aspects, but an impact of the Korean Wave on Indonesian culture could not be found.